Crossing borders - Watson, Elizabeth (New Zealand Science Review, 2009)
The title of this paper is a tribute to David Penny’s ability to cross borders: biology, mathematics, philosophy of science, history ... and the list goes on. The unknown for most people is exciting but fraught with fears. David it seems, is fearless; the unknown for him is the place to search for, until the territory is mapped, and then new unknown areas beckon. David has some good tools in his backpack to assist in his travels: curiosity, enthusiasm, intelligence, and an incredible stamina.